RNAi related mechanisms affect both transcriptional and posttranscriptional transgene silencing in Drosophila. - Pal-Bhadra, M.; Bhadra, U.; Birchler, J.A. (Molecular Cell, 2002)
Two types of transgene silencing were found for the Alcohol dehydrogenase (Adh) transcription unit. Transcriptional gene silencing (TGS) is Polycomb dependent and occurs when Adh is driven by the white eye color gene promoter. Full-length Adh transgenes are silenced posttranscriptionally at high copy number or by a pulsed increase over a threshold. The posttranscriptional gene silencing (PTGS) exhibits molecular hallmarks typical of RNA interference (RNAi), including the production of 21--25 bp length sense and antisense RNAs homologous to the silenced RNA. Mutations in piwi, which belongs to a gene family with members required for RNAi, block PTGS and one aspect of TGS, indicating a connection between the two types of silencing.